Does Digital Content Marketing and Destination Branding Improve Visit Intention - Lailatus Sa'adah, Siti; Maulidah, Silvana; Elita Dewi, Heptari; Asmara, Rosihan (Profit: Jurnal Adminsitrasi Bisnis, 2025)
The lack of a social media marketing strategy was challenging for the destination. Café Sawah, as an agrotourism destination, lacks in managing social media, thus hampering the optimization of digital marketing. In response, the destination must improve its intention to visit. This research analyzes the influence of digital content marketing and destination branding on visit intention through electronic word of mouth. This research was designed as quantitative research using the SEM PLS method with a sample of 130 people.  The sampling technique uses purposive sampling. The data in this research was obtained through a survey using a questionnaire. The results show that digital content marketing has a significant effect influence on visit intention. Likewise, destination branding does not have a substantial impact on visit intention. Furthermore, digital content marketing does not significantly affect visit intention through EWOM mediation. Meanwhile, destination branding significantly affects visit intention through EWOM mediation. Then, in the mediation test, Electronic Word of Mouth (EWOM) as a mediator between digital content marketing and visit intention could not mediate.